2021
DOI: 10.1161/jaha.121.020896
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effect of Circadian Rhythm Disorder on Reparative Angiogenesis in Hind Limb Ischemia

Abstract: Background Circadian rhythm disorders, often seen in modern lifestyles, are a major social health concern. The aim of this study was to examine whether circadian rhythm disorders would influence angiogenesis and blood perfusion recovery in a mouse model of hind limb ischemia. Methods and Results A jet‐lag model was established in C57BL/6J mice using a light‐controlled isolation box. Control mice were kept at a light/dark 12:12 (12‐hour li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…The Graph-Pad Prism software version 8.0 (GraphPad Software Inc) was used. Values of p < 0.05 were considered statistically significant [20].…”
Section: Discussionmentioning
confidence: 99%
“…The Graph-Pad Prism software version 8.0 (GraphPad Software Inc) was used. Values of p < 0.05 were considered statistically significant [20].…”
Section: Discussionmentioning
confidence: 99%
“…After overnight starvation, the cells were reseeded onto a 6‐well plate coated with Matrigel (Becton Dickinson, Bedford, MA) at 2×10 4 cells per well in EBM‐2 with 0.5% FBS medium. 22 The cells were incubated at 37 °C for 6 hours with DATS or vehicle, and morphological changes of LECs were microscopically analyzed in 3 different fields per well. Tube formation was assessed by the average of total tube lengths formed in the 3 fields per sample using Image J software (version 1.51).…”
Section: Methodsmentioning
confidence: 99%
“…Following research explored the impact of Per2 in EPCs (endothelial progenitor cells); Per2 −/− EPCs displayed impaired proliferation, migration, tube formation, and adhesion ( Sun et al, 2014 ). Jet lag plays an antiangiogenic role and inhibits blood reperfusion after ischemic injury; further loss-of-function studies explore the relation between Cry and HUVEC (human umbilical vein endothelial cell) phenotypes, which confirmed that knockdown of Cry1 and Cry2 in HUVECs inhibited proliferation, migration, and tubular morphological features ( Tsuzuki et al, 2021 ).…”
Section: Circadian System In Angiogenesismentioning
confidence: 73%
“…The human VEGF promoter activity follows a 24-h circadian pattern under the 12 h light–dark (LD) cycle, and the core circadian gene Bmal1 plays a transcriptional role by targeting the region of the VEGF promoter ( Jensen et al, 2012 ). In addition, the fluctuation of the serum VEGF level displayed a rhythmic pattern peaking during noon, while ECD induced by jet lag impaired this fluctuation by decreasing the VEGF serum level ( Tsuzuki et al, 2021 ). Moreover, Per2 and Cry1 act as critical rhythmic regulators of the hypoxia-induced expression of the VEGF; these observations indicate the existence of a negative feedback loop that rhythmically suppresses the transcriptional upregulation of VEGF under hypoxic conditions, resulting in the circadian fluctuation of VEGF expression and angiogenesis ( Koyanagi et al, 2003 ; Figure 4 ).…”
Section: Circadian System In Angiogenesismentioning
confidence: 99%